The Role of 21st century Learner Skills of Physical Education and Sports Teachers and Teacher Candidates on Teacher Skills - Ziya Bahadır; Ramazan Topuz; Zehra Certel (Türk Spor ve Egzersiz Dergisi)
ABSTRACTIn this study, the comparison of 21st century learner and teacher skills of physical education and sports teachers and teacher candidates and the role of 21st century learner skills on 21st century teacher skills were examined. Research is in relational scanning model. The sample of the study consists of 171 physical education and sports teachers working in Kayseri province and 184 students who are physical education and sports education students of Erciyes University Faculty of Sport Sciences. In this research, 21st learner skills use scale developed by Göksün (10) and 21st century teacher skills use scale developed by  Göksün (10) were used as the data collection tool. T-test and multiple regression analysis were used for data analysis. According to the findings, there was no significant differences in 21st century learner skills of teacher and teacher candidates, but significant differences were found in 21st century teacher skills. While the 21st century teachers' skills are predicted by innovative, cooperation and flexibility skills, the prospective teachers are predicted by cognitive skills.